Sixth Five Year Plan : Mid Term Appraisal - Planning Commission, Government of India (Planning Commission, Government of India, 1983)
The work of preparation of the Sixth Five Year Plan covering the period 1980—85 was taken up in April 1980. The Plan was approved by the National Development Council in February 1981 and presented to Parliament and the nation. Three years of the Plan have now been completed. A mid-term appraisal of a Five Year Plan is normally conducted half-way through its progress. Thus, the mid-term appraisal of the Sixth Five Year Plan 1980—85 should have been presented sometime towards the latter half of 1982. As is known, however, adverse weather in the kharif season of 1982 affected agricultural production, which is by far the most important component of the economy.
Government of India Planning Commission
Government of India Planning Commission
Keywords: Sixth Five Year Plan- India